2015
DOI: 10.1111/bjd.13424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of cysteamine 5% cream in the treatment of epidermal melasma: a randomized double-blind placebo-controlled trial

Abstract: Cysteamine cream showed significant efficacy in the treatment of melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(121 citation statements)
references
References 34 publications
4
113
0
4
Order By: Relevance
“…A double‐blind, randomized, vehicle‐controlled clinical study performed by Mansouri et al in 2015 on 50 melasma patients showed significant efficacy of cysteamine for the treatment of melasma . A second well‐controlled clinical trial also confirmed the efficacy of cysteamine for melasma treatment …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A double‐blind, randomized, vehicle‐controlled clinical study performed by Mansouri et al in 2015 on 50 melasma patients showed significant efficacy of cysteamine for the treatment of melasma . A second well‐controlled clinical trial also confirmed the efficacy of cysteamine for melasma treatment …”
Section: Discussionmentioning
confidence: 90%
“…Body cells produce cysteamine through the conversion of coenzyme A to pantethine which is then broken to cysteamine. 6 The depigmenting action of cysteamine has been shown by Chavin et al 7,8 and Frank et al 9 Their findings were indicative of a more potent depigmenting affect for cysteamine com- Considering the results of the two well-controlled clinical studies that confirm its efficacy in the treatment of melasma 13,14 and its high safety profile, cysteamine might replace mutagenic and potentially hazardous depigmenting agents in future.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent change in the formulation of cysteamine led to the reduction in the sulfur odor and skin irritability, allowing its use as a cream that has proven to be effective in the topical treatment of melasma. [11][12][13] However, to date no study has compared this formulation of topical cysteamine to 4% hydroquinone in the treatment of melasma.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized, double-blind trial of 40 patients, a significant improvement in melasma lesions was observed compared with patients who were treated with placebo. Mansouri et al (2015) assessed the efficacy of 5% cysteamine in 50 patients with melasma. Cysteamine induced significant reductions in MASI scores at 16 weeks compared with placebo.…”
Section: New Topical Agentsmentioning
confidence: 99%